MENINGKATKAN KETERAMPILAN MENYUSUN PERANGKAT AJAR BERBASIS HOTS MELALUI LOKAKARYA MODEL CERDAS - Marianus Tapung; Marselus R. Payong; Agustinus Naba Susanto (LPPM Universitas Bina Bangsa, 2024)
This Community Service (PkM) activity was made, departing from diagnostic assessment information that the teachers of SMAK St. Ignatius Loyola West Manggarai still experience a lack of understanding in compiling HOTS-based learning tools. Based on an agreement with the school and the PkM Team of St. Paul Ruteng Catholic University Lecturers, an intervention was carried out by making a workshop for the preparation of Higher Order Thinking Skills (HOTS)-based teaching tools. In order for this activity to be meaningful and impactful, effective and efficient, the CERDAS (Collaborative, Educational, Responsive, Dynamic, Adaptative, Smart) model is used. This model is very helpful for teachers in processing and producing teaching tools in the form of lesson plans, teaching modules and assessment tools. The results of feedback conducted during and after the activity illustrate that the ability to collaborate, respond to student needs, dynamic and adaptive in planning and learning from teachers has been included in the